4CPS-059 Efficacy and safety of early switch to oral antibiotherapy in pneumology: propensity score-matched analysis. Issue 1 (23rd March 2023) - Echeverría, D; Rodriguez, A; Domínguez, M; Ausin, P; Balcells, E; Miedes, J; Gómez-Zorrilla, S; Horcajada, JP; Grau, S
Abstract : Background and Importance: Sequential intravenous-to-oral antibiotic therapy has been associated to numerous benefits. This strategy has not been studied in the case of patients with lung disease whose late resolution of respiratory failure could delay the switch to oral treatment. Aim and Objectives: The aim of this study was to evaluate the efficacy and safety of early switch to oral antibiotherapy in pneumology department. Material and Methods: Quasi-experimental study before-after in a tertiary hospital. The protocol was established by Antimicrobial Stewardship Program in February 2018. Inclusion criteria: intravenous antibiotic treatment potentially modifiable to oral administration at the time of admission to pneumology. Before-group included patients from December 2015 to February 2018. After-group from March 2018. Data expressed by mean (standard deviation) and absolute frequencies. Propensity score matching adjusted by age, pulmonary hypertension, gender and pulmonary fibrosis. Non-parametric methods were performed for hospital stay, expressed by median (Q1-Q3). Results: A total of 286 patients were included (105 before-group, 181 after-group). Age 69.9 (12.7) years, women 40.6%. SAPSII 28.8 (8.1), FEV1 48.5 (19.1). No significant differences were observed between groups. Pneumonia (18.7% vs 18%, [CURB-65 2 vs 1, p=0.290]), COPD exacerbation (51.4% vs 60%, p=0.351), broncho aspiration (11.2% vs 14%, p=0.120). Beta-lactams 62.2%, quinolones 31.1%, clindamycin 2.1%. In after-group, 5.5% patients were in semi-critical unit. No oxygen therapy 27.1%, nasal cannula 37.6%, ventimask 37.6%, noninvasive mechanical ventilation 1.7%. Hospital stay was lower after protocol implementation: 8 (6-13) vs 10 (7-15) days (p=0.120), also days of intravenous administration: 8.3 (4.9) vs 12.3 (19.1) days (p=0.007), days to oral administration: 3.6 (2.3) vs 5.3 (2.9) days (p=0.000), and treatment duration: 7.7 (4.1) vs 10.1 (4.2) days (p=0.000). No statistical significant differences were found in 7-day mortality, 30-day mortality, 30-day readmission or clinical cure. Clinical failure was due to superinfection (11.1% vs 40%, p=0.165), inadequate empirical treatment (77.8% vs 60%, p=0.211) and failure after switch to oral administration (11.1% vs 0, p=0.240). No differences observed in thrombophlebitis, catheter bacteremia or gastrointestinal toxicity incidence. Conclusion and Relevance: Despite not achieving statistical significance, probably because of the lack of statistical power, a 2-day reduction in hospital stay was observed. Early switch to oral antibiotherapy was safe without an increase in adverse events or worse clinical outcome. References and/or Acknowledgements: Conflict of Interest: No conflict of interest